Enhancing strength–ductility synergy in medium Mn steel with hetero-structured austenite developed by two-stage cyclic thermomechanical treatment and flash annealing. (15th March 2023) - Jia, Qixiang; Chen, Lei; Chen, Xiang; Choi, Howook; Xing, Zhibin; Lee, Siwhan; Kim, Hwangsun; Wang, Haoyu; Huang, Huagui; Jin, Miao; Han, Heung Nam
Abstract: In this study, a novel and efficient processing strategy involving a two-stage thermomechanical process and flash annealing (FA) was applied to medium Mn steel (MMnS) to achieve hetero-structure with a tailored dislocation distribution, resulting in considerably enhanced strength–ductility synergy. Through the observations of in-situ electron backscattering diffraction (EBSD) and transmission electron microscopy (TEM), it is confirmed that FA can heterogeneously distribute dislocations between coarse and fine-grained austenite by inhibiting recrystallization and martensitic reverse transformation. Furthermore, the high dislocation density in austenite of FA-processed MMnS increased the yield strength by almost 1.7 times compared to MMnS subjected to conventional intercritical annealing (IA). Hetero-deformation and transformation-induced plasticity were induced in heterostructured austenite, which improved strain hardening ability and corresponding ductility. This study offers a unique process method for heterostructured microstructure design for multiphase steels with metastable austenite to remarkably enhance mechanical performance. Graphical abstract: Image, graphical abstract